Sustained health home visiting can improve families' social support and community connectedness. Issue 2 (6th May 2016) - Stubbs, Joanne M.; Achat, Helen M.
Abstract : Background : Home visiting (HV) is a strategy used internationally to address the multiple needs of infants and families at risk of suboptimal health and developmental outcomes. Objectives : Describe nursing interventions and program achievements of a pilot HV program for families living in a highly disadvantaged outer suburb of Sydney, New South Wales, Australia. Methods : A family partnership model was adopted. Follow-up is reported for 65 of the 75 clients remaining in the program for at least 6 months. Results : Nurses most commonly provided clients with emotional support, information about health and well-being and information on infant development. Clients experienced noteworthy improvements consistent with key objectives – greater access to support services, and increased self-efficacy and social networks. Conclusions : Consistent with the growing body of international literature on the achievements of HV, HV programs can empower vulnerable families to better cope with daily life demands and their family.